Fly away home - Bunting, Eve, 1928-; Himler, Ronald (New York : Clarion Books, 1991)
A homeless boy who lives in an airport with his father, moving from terminal to terminal and trying not to be noticed, is given hope when he sees a trapped bird find its freedom.
450
Accelerated Reader AR
Keywords: Homeless persons -- Fiction; Airports -- Fiction; Birds -- Fiction